2020
DOI: 10.1016/j.ijid.2020.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Inoculum at the time of SARS-CoV-2 exposure and risk of disease severity

Abstract: A relationship between the infecting dose and the risk of disease severity has not been demonstrated for SARS-CoV-2 infection. Here, we report three clusters of individuals that were potentially exposed to distinct inoculum in Madrid. Overall each group developed divergent clinical forms of COVID-19. Our data support that a greater viral inoculum at the time of SARS-CoV-2 exposure might determine a higher risk of severe COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 11 publications
3
104
0
5
Order By: Relevance
“…First, a very high dose of virus might have led to the second instance of infection and induced more severe disease. 23 Second, it is possible that reinfection was caused by a version of the virus that was more virulent, or more virulent in this patient's context. Third, a mechanism of antibody-dependent enhancement might be the cause, a means by which specific Fc-bearing immune cells become infected with virus by binding to specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…First, a very high dose of virus might have led to the second instance of infection and induced more severe disease. 23 Second, it is possible that reinfection was caused by a version of the virus that was more virulent, or more virulent in this patient's context. Third, a mechanism of antibody-dependent enhancement might be the cause, a means by which specific Fc-bearing immune cells become infected with virus by binding to specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that difficulty, emerging evidence consistent with a dose-response relationship between the infecting dose and disease severity has been recently observed in three clusters of individuals that were exposed to diverse inocula and developed divergent clinical forms of COVID-19 disease. [27] The potential infecting doses were determined by the extent of physical distancing and precautionary measures that the individuals followed. It was evident that in the clusters which did not follow physical distancing or other precautions, such as wearing masks, a larger proportion of individuals developed severe disease, whereas only asymptomatic or mild disease was seen in the cluster, where exposure had been low.…”
Section: Emerging Evidence From Sars-cov-2/covid-19mentioning
confidence: 99%
“…It was evident that in the clusters which did not follow physical distancing or other precautions, such as wearing masks, a larger proportion of individuals developed severe disease, whereas only asymptomatic or mild disease was seen in the cluster, where exposure had been low. [27] …”
Section: Emerging Evidence From Sars-cov-2/covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The association between viral load and clinical outcome including severity of symptoms is still poorly characterized although the majority of studies reported an association between higher viral loads and more severe symptoms [11][12][13][14][15][16][17][18][19].…”
Section: Association Of Viral Load With Symptoms and Outcomementioning
confidence: 99%